Using the Fuzzy Analytic Hierarchy Process (FAHP) for Evaluating the Factors Affecting Building Rehabilitation Cost Management in Iraq (Journal of Engineering, 2025)
This research aims to evaluate the factors affecting building rehabilitation cost management using the fuzzy analytical hierarchy process (FAHP) model. A literature review, case studies, consultations with experts, and questionnaires were used to identify and categorize fifty-seven factors into six categories. The proposed model has considered twenty factors out of the fifty-seven. The main factor with the highest weight in building rehabilitation cost management in Iraq is the building characteristics, with a weight of 0.298. Design and bill of quantities issues follow this with a weight of 0.204. The next factor is project management Issues with a weight of 0.185. Planning and contract management factors come next with a weight of 0.150. Safety and environmental factors have a weight of 0.104. The element with the lowest weight is economic and financial factors, with a weight of 0.058. This order of elements highlights their importance in affecting cost management. The prioritization within each category is outlined with due consideration to the weights assigned to the main factors. The significance of required quality standards and site visit to the building under the design and bill of quantities, while planning and contract management prioritize project duration and general and specific contract conditions. Building characteristics prioritize the number of floors in the building and its location, economic and financial factors emphasize fluctuations in currency exchange rates and labor costs, and safety and environmental concerns are anchored by health, safety, awareness and training. Project management emphasizes change orders and a lack of coordination among team.